SEMA3C Promotes Cervical Cancer Growth and Is Associated With Poor Prognosis - Liu, Ruoyan; Shuai, Yanjie; Luo, Jingtao; Zhang, Ze (Frontiers in Oncology, 2019)
Aberrant activation of Semaphorin3C(SEMA3C) is widespread in human cancers. We investigate the role of SEMA3C in cervical cancer and its underlying mechanism. Materials and methods The expression of SEMA3C was examined in paraffin cervical cancer specimens. Invivo and in vitro assays were performed to validate the effect of SEMA3C on cervical cancer cell proliferation and p-ERK pathway activation.Gene Set Enrichment Analysis (GSEA) was performed using The Cancer Genome Atlas (TCGA) data set. Results SEMA3C expression is associated with poor survival both in TCGA cohort and our cohort. Silencing of SEMA3C suppressed cervical cancercell proliferation,colony formation ability and the activation of p-ERK signaling pathway in vitro. SEMA3C depletioninhibited tumor growth in vitro. GSEA also showed that epithelial mesenchymal transition (EMT), TGFβ signaling pathway, angiogenesis, and extracellular matrix (ECM) receptor interaction are associated with SEMA3C high expression phenotype. Conclusion SEMA3C is correlated with poor prognosis of cervical cancer patients and promotes tumor growth via the activation of p-ERK pathway.